ANALISIS PENGELOLAAN ZAKAT OLEH BAZNAS KOTA SINGKAWANG BERDASARKAN PRINSIP KEADILAN DISTRIBUTIF DALAM MAQASHID SYARI’AH - Anyta Widianti; Andi Muhammad Akmal; Jamiat Akadol (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Zakat as an Islamic financial instrument not only functions as worship, but also has a strategic role to embody social justice. The purpose of this research is to analyze the zakat management by BAZNAS Singkawang city based on the principle of distributive justice in the perspective of maqashid sharia. This research is an empirical research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results indicate that the management of zakat by BAZNAS Singkawang has attempted to fulfill the principle of distributive justice through equal distribution to all ashnaf groups by direct assistance programs based on the needs and potential of mustahik. However, the management of zakat by BAZNAS Singkawang based on the principle of distributive justice in maqashid sharia still faces obstacles and challenges in terms of equalizing the needs of mustahik so that comprehensive mapping is required in the distribution of zakat. Long term zakat management planning by prioritizing the maqashid sharia approach is also needed to create economic transformation and empowerment of mustahik.